HUBUNGAN PENGETAHUAN DAN SIKAP WANITA PUS DENGAN KEJADIAN PERNIKAHAN DINI DI DESA LANJAN KECAMATAN SUMOWONO KABUPATEN SEMARANG TAHUN 2013 - Alan Darmasaputra; Raden Djoko; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Early marriage was one of the population problems that occurred in many countries. Early marriage was carried out in their marriage before the age of 20 years for women and 25 years for men. In 2013, there were 38.28% were married all marriages recorded at KUA sumowono. Lanjan village was the village with the highest number of early marriages 19.14%. The purpose of this study was to analyze the relationship between knowledge and attitudes of women of childbearing age couple with incident early marriage in the District Lanjan village Sumowono District Semarang District. This research is explanatory research with cross sectional study design. Population and sample in this study were women of childbearing age couples who perform marriages in the period of 2013 were 46 women with the incidence of early marriage which amounted to 20 people. Data were analyzed with univariate and bivariate with chi square test with Yates correction method with a significance level α = 5%The results showed that the analysis of the percentage of couples of reproductive age women the knowledge less well (86.9%), the attitude of women of reproductive age couples less well (84.7%). Result of chi square test with Yates correction method is no association with the incidence of pus woman knowledge of early marriage (p value = 0.894) and No association pussy female attitude to the events of early marriage (p value = 1.000).The advice given is known that early marriage because society pregnant outside of marriage can therefore be followed up by examining the driving factors that lead to early marriage.